PENGARUH INVESTASI DAN DEPENDECY RATIO TERHADAP PENGANGGURAN DI KABUPATEN MIMIKA - Tri apriyono; Yahya Nusa (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2021)
This research was conducted with the aim of developing a theoretical empirical model that analyzes the effect of investment and dependency ratio on unemployment in Mimika Regency. The research method used is the associative method. The data collection technique used to obtain data in this research is documentation technique. To measure the effect of investment and dependency ratio on unemployment in Mimika Regency, multiple linear regression analysis was used. The results of this study indicate that investment and dependency ratio have no effect on unemployment in Mimika Regency